Strain-induced step bunching in orientation-controlled GaN on Si. (8th March 2016) - Narita, Tetsuo; Iguchi, Hiroko; Horibuchi, Kayo; Otake, Nobuyuki; Hoshi, Shinichi; Tomita, Kazuyoshi
Abstract: We report a technique for the fabrication of high-quality GaN-on-silicon (Si) substrates for use in various power applications. GaN epitaxial layers were generated on Si(111) vicinal faces that had been previously covered with a thin coating of Al2 O3 to control the orientation of the AlN seed layers. We obtained orientation-controlled GaN layers and found a linear relationship between the GaN c -axis and Si[111] tilt angles. As a result, the threading dislocation density in the AlN seed layer was reduced and high-quality GaN layers were generated. The X-ray rocking curves for these layers exhibited full width at half maximum values of 390′′ and 550′′ for the (004) and (114) reflections, respectively. Significant step bunching was observed on a GaN(0001) vicinal face produced using this technique, attributed to strain-induced attractive interactions between steps. Thus, by controlling the strain near the surface layer, we achieved the step flow growth of GaN on Si.